Escape from the deep : the epic story of a legendary submarine and her courageous crew - Kershaw, Alex (Da Capo Press, 2008)
Details the history of the U.S. Navy submarine Tang in the Pacific theater of World War II, the explosion that led to its sinking, the ordeal of its surviving crew members and their capture by the Japanese, followed by months of brutal captivity.